2008
DOI: 10.1016/j.freeradbiomed.2008.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Methionine sulfoxide reductase A protects dopaminergic cells from Parkinson's disease-related insults

Abstract: Parkinson's disease (PD) is a neurologic disorder characterized by dopaminergic cell death in the substantia nigra. PD pathogenesis involves mitochondrial dysfunction, proteasome impairment, and α-synuclein aggregation, insults that may be especially toxic to oxidatively stressed cells including dopaminergic neurons. The enzyme methionine sulfoxide reductase A (MsrA) plays a critical role in the antioxidant response by repairing methionine-oxidized proteins and by participating in cycles of methionine oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 57 publications
2
94
0
Order By: Relevance
“…It has even been hypothesized that α-synuclein itself, through its reversible methionine oxidation and reduction driven by methionine sulfoxide reductase (Msr), may serve as a cellular antioxidant [148] by transferring oxygenbased radicals that are generated in modest amounts at cell membranes (i.e., lipid peroxidation products) to more stable and easily contained carbon-centered radicals [149]. This notion is consistent with findings that increased expression of MsrA in Drosophila prevents α-synuclein-dependent locomotor and circadian rhythm deficits [150] and MsrA protects against mutant α-synuclein-induced toxicity in cultured cells [151]. A thorough review of the oxidative and nitrative changes that occur in α-synuclein and their effects on aggregation and toxicity is the subject of a recent review [147].…”
Section: Oxidation and Nitrationsupporting
confidence: 77%
“…It has even been hypothesized that α-synuclein itself, through its reversible methionine oxidation and reduction driven by methionine sulfoxide reductase (Msr), may serve as a cellular antioxidant [148] by transferring oxygenbased radicals that are generated in modest amounts at cell membranes (i.e., lipid peroxidation products) to more stable and easily contained carbon-centered radicals [149]. This notion is consistent with findings that increased expression of MsrA in Drosophila prevents α-synuclein-dependent locomotor and circadian rhythm deficits [150] and MsrA protects against mutant α-synuclein-induced toxicity in cultured cells [151]. A thorough review of the oxidative and nitrative changes that occur in α-synuclein and their effects on aggregation and toxicity is the subject of a recent review [147].…”
Section: Oxidation and Nitrationsupporting
confidence: 77%
“…Thus, MsrA may act as a new number in the vitagenes network for its cytoprotection and inducible expression during stressful conditions. Previous studies have revealed that enhancing MsrA function may be beneficial in Parkinson's disease (PD) and Alzheimer's disease (AD) via scavenging ROS and repairing methionine sulfoxide (35,43,64). Taken together, our results suggest that MsrA negatively controls microglia-mediated neuroinflammation, and pharmacological enhancement of MsrA function may serve as a reasonable therapeutic strategy aimed at reducing neurodegeneration in the clinic.…”
Section: Discussionsupporting
confidence: 58%
“…None of the antioxidants protected against the cellular toxicity of -syn in yeast (supplementary material Figs S6-S8). Similarly, these antioxidants did not protect against the toxicity of -syn in the nematode or rat midbrain neuronal culture models (Liu et al, 2008b) (supplementary material Figs S9 and S10). Thus, rescue of toxicity by these compounds is not due to simple antioxidant activity.…”
Section: Chemical Suppressors Of -Syn Toxicity Reverse Mitochondrialmentioning
confidence: 96%